Sensitivity of tropical cyclone damage costs to integrated wind profile - Cao Wang (Journal of Ocean Engineering and Science, 2021)
The dramatic tropical cyclone (TC) damages in coastal areas around the world have gained significant attention from asset owners, policy makers and engineers. The estimate of TC damage for a specific region of interest is informative of the preparedness and resilience of the area subjected to TC hazards, and thus should be conducted using a quantitative approach. A reasonable indicator of TC damage should incorporate not only the TC characteristics (e.g., intensity, frequency and duration) but also the vulnerability of the TC-prone areas. In this paper, a new indicator is proposed to measure the TC threat, which takes into account both the TC characteristics and the vulnerability of the area. The indicator has two forms: the first one considers the maximum wind speed only and the second incorporates the integrated wind speed profile. The historical damage scenarios along the US East Coast, as well as those in Hong Kong, China, are examined to demonstrate the applicability of the proposed indicator. Results show that the proposed indicator is capable of representing the impact of TC wind field profile on the TC damage costs. The proposed indicator could be further used to project the future TC damages for areas subjected to TC hazards.